Rethinking surface reactions in nanoscale dry processes toward atomic precision and beyond: a physics and chemistry perspective. (30th May 2019) - Ishikawa, Kenji; Ishijima, Tatsuo; Shirafuji, Tatsuru; Armini, Silvia; Despiau-Pujo, Emilie; Gottscho, Richard A.; Kanarik, Keren J.; Leusink, Gert J.; Marchack, Nathan; Murayama, Takahide; Morikawa, Yasuhiro; Oehrlein, Gottlieb S.; et al.
Abstract: In this review, we discuss the progress of emerging dry processes with atomic precision. Researchers in the field of plasma processing and surface science have addressed the increasingly challenging demands of material selectivity by utilization of synergistic enhancement of etching or deposition. The discussion encompasses major challenges in the plasma science and technology community. The focus of the review is advances in atomic layer etching and area-selective deposition with activation or deactivation, especially in terms of materials scaling and variety. Control of high-aspect-ratio feature fabrication in semiconductor manufacturing and etched shapes of interior features at the nanoscale are needed. Issues related to profile distortion have received much attention. State-of-the-art techniques used in semiconductor manufacturing are reviewed and future challenges are outlined.